The influence of school inclusive education climate on physical education teachers’ inclusive education competency: The mediating role of teachers’ agency - Xue, Rui; Chai, Hongqin; Yao, Lei; Fu, Wangqian (Frontiers in Psychology, 2023)
Teachers’ inclusive education (IE) competency is the key to the successful implementation of IE. Under the background of China’s vigorous development of IE, the influence mechanism of IE competency of Chinese physical education (PE) teachers has not been paid attention to. The present study concentrates on the relationships between school IE climate, PE teachers’ agency, and IE competency. Data were collected from 286 primary and junior high school PE teachers through nationwide convenience sampling on the Internet in China by completing the School IE Climate Scale, PE Teachers’ Agency Scale, PE Teachers’ IE Competency Scale. Results of structural equation modelling revealed that school IE climate had a significant effect on PE teachers’ agency; School IE climate was a significant influence on PE teachers’ IE competency; The mediation effect of PE teachers’ agency on the relationship between school IE climate and IE competency was significant as well. These results demonstrate that school IE climate plays a direct and indirect role in promoting PE teachers’ IE competency.